Arterial Switch Operation With Neoaortic Valve Replacement in a 13-Year Old Patient With Transposition of Great Arteries With Ventricular Septal Defect and Left Ventricular Outflow Tract Obstruction—A Case Report. Issue 4 (July 2020) - Chowdhuri, Kuntal Roy; Daga, Manoj Kumar; Mandal, Subhendu; Das, Pravir; Hoque, Amanul; Meur, Saumen; Gorain, Somenath; Dutta, Nilanjan; Iyer, Krishna Subramony
The surgical management ofd -transposition of great arteries (d- TGAs) with ventricular septal defect (VSD) and left ventricular outflow tract obstruction (LVOTO) is ever evolving and still remains a challenge because of wide anatomic variability, age of presentation, surgical options available, and their variable long-term results in different series. We describe a patient withd- TGA, VSD, and LVOTO who presented to us at 13 years of age and underwent an arterial switch operation along with neoaortic valve replacement with a mechanical prosthesis. The postoperative course was uneventful, and at hospital discharge, the echocardiogram was satisfactory. We present the pros and cons of this hitherto undescribed treatment option.